Ultracentrifugation studies on the transmembrane domain of the human erythrocyte anion transporter band 3 in the detergent C12E8. - Cölfen, H; Boulter, J; Harding, SE; Watts, A (1998)
The dilute solution behaviour of the transmembrane domain (TMD) of the human erythrocyte anion exchanger Band 3 was studied by analytical ultracentrifugation. Sedimentation velocity and equilibrium studies of the TMD solubilized with the detergent C12E8 demonstrate that the protein is a stable dimer in the concentration range 0.1 to 1 mg/ml. There is no evidence of a dissociation at low concentrations or of an association at higher concentrations. Hydrodynamic calculations applying a prolate ellipsoid of revolution and assuming a hydration of w = 0.35 result in an asymmetrical particle with an axial ratio (a/b) of approximately 3.5.